Tumor mitochondria-targeted photodynamic therapy with a translocator protein (TSPO)-specific photosensitizer. (December 2015) - Zhang, Shaojuan; Yang, Ling; Ling, Xiaoxi; Shao, Pin; Wang, Xiaolei; Edwards, W. Barry; Bai, Mingfeng
Graphical abstract: Abstract: Photodynamic therapy (PDT) has been proven to be a minimally invasive and effective therapeutic strategy for cancer treatment. It can be used alone or as a complement to conventional cancer treatments, such as surgical debulking and chemotherapy. The mitochondrion is an attractive target for developing novel PDT agents, as it produces energy for cells and regulates apoptosis. Current strategy of mitochondria targeting is mainly focused on utilizing cationic photosensitizers that bind to the negatively charged mitochondria membrane. However, such an approach is lack of selectivity of tumor cells. To minimize the damage on healthy tissues and improve therapeutic efficacy, an alternative targeting strategy with high tumor specificity is in critical need. Herein, we report a tumor mitochondria-specific PDT agent, IR700DX-6T, which targets the 18 kDa mitochondrial translocator protein (TSPO). IR700DX-6T induced apoptotic cell death in TSPO-positive breast cancer cells (MDA-MB-231) but not TSPO-negative breast cancer cells (MCF-7). In vivo PDT study suggested that IR700DX-6T-mediated PDT significantly inhibited the growth of MDA-MB-231 tumors in a target-specific manner. These combined data suggest that this new TSPO-targeted photosensitizer has great potential in cancer treatment. Statement of Significance: Photodynamic therapy (PDT) is an effective and minimally invasive therapeutic technique for treating cancers. Mitochondrion is an attractive target for developing novel PDT agents, as it produces energy to cells and regulates apoptosis. Current mitochondriatargeted photosensitizers (PSs) are based on cationic molecules, which interact with the negatively charged mitochondria membrane. However, such PSs are not specific for cancerous cells, which may result in unwanted side effects. In this study, we developed a tumor mitochondria-targeted PS, IR700DX-6T, which binds to translocator protein (TSPO). This agent effectively induced apoptosis in TSPO-positive cancer cells and significantly inhibited tumor growth in TSPO-positive tumor-bearing mice. These combined data suggest that IR700DX-6T could become a powerful tool in the treatment of multiple cancers that upregulate TSPO.